2016
DOI: 10.1016/j.jphotobiol.2016.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazinium photosensitisers XI. Improved toluidine blue photoantimicrobials

Abstract: The phenothiazinium derivative toluidine blue O (TBO) is widely employed as a photoantimicrobial agent in clinical trialling, particularly in dentistry. However, its activity against a range of pathogenic microbial species is not significantly different to that of the standard photoantimicrobial methylene blue. In the current study, derivatives of TBO with varying hydrocarbon substitution in chromophore position 2 were synthesised via the established anilinethiosulphonic route, using the mild oxidant silver(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…For the aPDT treatment and PS in the absence of light, irrigation with 0.3 mL BuTB was performed at three concentrations: 0.1 mg/mL, 0.5 mg/mL and 2 mg/mL. The photosensitizer BuTB was synthesized as previously reported (16). Irrigation was carried out with the aid of an insulin syringe, carefully directing the tip of the needle into the tooth / gingival tissue following homeostasis of the area.…”
Section: Bubt and Antimicrobial Photodynamic Therapy (Apdt)mentioning
confidence: 99%
See 2 more Smart Citations
“…For the aPDT treatment and PS in the absence of light, irrigation with 0.3 mL BuTB was performed at three concentrations: 0.1 mg/mL, 0.5 mg/mL and 2 mg/mL. The photosensitizer BuTB was synthesized as previously reported (16). Irrigation was carried out with the aid of an insulin syringe, carefully directing the tip of the needle into the tooth / gingival tissue following homeostasis of the area.…”
Section: Bubt and Antimicrobial Photodynamic Therapy (Apdt)mentioning
confidence: 99%
“…The present study demonstrates for the first time the in vivo effects of three concentrations of a new PS. Butyl toluidine blue (BuTB) was developed by physicochemical modifications of the molecular structure of the established phenothiazine dye toluidine blue O (TBO) (16). Previously evaluated for photoantimicrobial activity (16), BuTB was evaluated here as a photosensitizing agent for in vivo aPDT, as an adjuvant to SRP, in the treatment of experimental periodontitis (EP) in rats.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Novel derivatives, such as the pentacyclic S137, and derivatives with basic side chains, more effective than the lead compound MB are still being synthesized [38][39]. Previous studies have reported that APDT with phenothiazinium derivatives kills different fungal structures, such as microconidia of different species including the dermatophyte Trychophyton spp.…”
Section: Dimidiatum Was Isolated From Environmental Samples and Patiementioning
confidence: 99%
“…PSs can be activated by visible light of a specific wavelength to initially form the excited singlet state, followed by transition to the longer-lived excited triplet state (17). This triplet state can undergo photochemical reactions in the presence of oxygen via Type I photochemical mechanisms (electron transfer to produce superoxide, hydrogen peroxide, and hydroxyl radicals), typical of phenothiazinium dyes (18), or Type II mechanisms (energy transfer process), typical of porphyrins (19,20), and Rose Bengal (21,22). Reactive oxygen species (ROS) can oxidize lipids, proteins, and nucleic acids, leading to cell damage and death through necrosis where cells swell and lyse to release their intracellular content causing inflammation, or alternatively cells can undergo apoptosis (23,24).…”
Section: Introductionmentioning
confidence: 99%